AN UNUSUAL FOREIGN BODY IN THE ESOPHAGUS - D. M. Mustafaev (Неотложная медицинская помощь, 2016)
ABSTRACT. Sharp and sharppointed foreign bodies in the aerodigestive tract can result in potentially fatal complications. They can be safety removed by rigid esophagoscopy thereby avoiding open surgical methods, which may be required when there is perforation or abscess formation. This case report highlights the risk of accidental ingestion of various dental instruments, which can lead to fatal complications. Successful removal of a foreign body helped prevent the development of lifethreatening complications.